Expanding Language Development Among Children And Communication Disorders - Nur Hayati Yusuf; Pingkan Titania Patmawati (PROCEEDING UMSURABAYA, 2020)
Abstract : Language development disorder is the inability or limitations in using linguisticsymbols to communicate verbally or delays in children's speech and language development abilities according to their age group, gender, customs and intelligence. Therefore, if speech and base disorders are not treated properly, there will be impaired reading ability, verbal ability, behavior, psychosocial adjustment, and poor academic ability. Parents or teachers need to understand this problematic behavior because "problematic children" usually appear in the classroom and they even show the problem in their behavior during interaction with the environment. Humans use language to communicate, socialize, and convey their thoughts. Early identification of language delays must solve two main problems namely the problem of the availability of reliable information from a child at some age when they experience limitations in communication skills. Furthermore, measurement techniques must be cost-effective by respecting time in a professional manner and widely able to be applied to children at various social levels and language backgrounds including bilingual. The second problem is the interpretation of the results of the identification process. Many children who experience language delays at the age of 24 to 30 months who will catch up in a few years later and do not need intervention. The challenge is to identify and use relevant information in improving diagnosis decisions regarding an individual child to prevent more significant developmental disorders.Keywords: language, communication, children